FORMATION OF RHETORICAL COMPETENCE AMONG STUDENTS OF NON-PHILOLOGICAL SPECIALITIES WITHIN PROFESSIONALLY ORIENTED DISCOURSE (Physical Culture and Sport: Scientific Perspective, 2025)
The article explores the process of developing rhetorical competence among students of non-philological specialities within the framework of professionally oriented discourse. The relevance of the study is determined by the need to train specialists capable of effective oral and written communication in their professional domain. Particular attention is paid to the interdisciplinary nature of rhetoric as a field of study that integrates linguistic, pedagogical, psychological, and cultural components.The concept of “rhetorical competence” is analysed through the lens of the communicative paradigm of modern education. Its core components are identified, including the ability to construct logically complete and structured utterances, adherence to ethical norms of communication, and the skill of exerting persuasive influence on the interlocutor. It is substantiated that rhetorical competence is an essential element of the professional speech culture of non-philology students, as it ensures adequate perception, interpretation, and production of information in a professional context.The article outlines methodological approaches to developing rhetorical skills in the process of teaching the Ukrainian language for professional purposes. Emphasis is placed on interactive forms of learning such as discussions, debates, role-playing, and speech training sessions, which promote students' cognitive engagement and the formation of oral professional speech skills. The article also presents examples of educational tasks and communicative exercises tailored to the specifics of non-philological disciplines.The study concludes that rhetorical competence can be purposefully developed by creating conditions for the practical application of speech skills in settings that simulate real professional communication. Further research may focus on the development of comprehensive instructional materials aimed at integrating rhetorical practices into the curriculum of Ukrainian for Specific Purposes.
Keywords: rhetorical competence; professionally oriented discourse; non-philological students; Ukrainian for Specific Purposes; speech culture; communicative activity